Determinasi Kinerja Pegawai Pajak pada KPP Pratama Badung Utara : Peran Strategis Beban Kerja, Kepuasan Kerja, dan Motivasi Kerja - Dini Novianti; Kadek Rai Suwena; Trianasari Trianasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
Public sector organisations face increasingly strong accountability demands, making employee performance an important aspect that must be maintained consistently. KPP Pratama Badung Utara, as a vertical unit of the Directorate General of Taxes, is required to demonstrate stable performance, especially on indicators related to stakeholder and customer perspectives. However, the Organizational Performance Value (NKO) data for the 2022–2024 period shows a decline in several key indicators, indicating the need for an evaluation of internal employee factors. This study examines the role of workload, job satisfaction, and work motivation in explaining variations in the performance of KPP Pratama Badung Utara employees. The study uses a quantitative approach through a survey with a Likert scale questionnaire instrument. The data were analysed using validity and reliability tests, classical assumption tests, and multiple linear regression to test the simultaneous and partial effects between variables. The results of the study indicate that workload, job satisfaction, and work motivation collectively influence employee performance. Partially, job satisfaction and work motivation are proven to be factors that drive performance improvement, while workload shows a relationship that needs to be managed proportionally so as not to reduce productivity. These findings highlight the importance of human resource management strategies in the public sector through proper workload distribution, enhancement of job satisfaction, and development of employee motivation to support sustainable organisational performance.